2018
DOI: 10.1152/jn.00084.2018
|View full text |Cite
|
Sign up to set email alerts
|

Muscle coactivation: definitions, mechanisms, and functions

Abstract: The phenomenon of agonist-antagonist muscle coactivation is discussed with respect to its consequences for movement mechanics (such as increasing joint apparent stiffness, facilitating faster movements, and effects on action stability), implication for movement optimization, and involvement of different neurophysiological structures. Effects of coactivation on movement stability are ambiguous and depend on the effector representing a kinematic chain with a fixed origin or free origin. Furthermore, coactivation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
147
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 178 publications
(178 citation statements)
references
References 151 publications
2
147
1
Order By: Relevance
“…In this vein, several studies on deafferented monkeys (without feedback circuitry at all) suggested that an equilibrium point/trajectory resulting from the co-contraction of agonist and antagonist mus- Similar conclusions were drawn with deafferented patients who were able to perform relatively accurate reaching movements without on-line vision -if allowed to see their arm transiently prior to movement execution- [41]. Furthermore, neurophysiological studies seem to agree that co-contraction commands have a central origin with little contribution from spinal mechanisms [14,19,42]. Noticeably, during cocontraction of opposing muscles, disynaptic reciprocal inhibition has been shown to be reduced by central signals [43,44].…”
Section: Introductionmentioning
confidence: 53%
See 4 more Smart Citations
“…In this vein, several studies on deafferented monkeys (without feedback circuitry at all) suggested that an equilibrium point/trajectory resulting from the co-contraction of agonist and antagonist mus- Similar conclusions were drawn with deafferented patients who were able to perform relatively accurate reaching movements without on-line vision -if allowed to see their arm transiently prior to movement execution- [41]. Furthermore, neurophysiological studies seem to agree that co-contraction commands have a central origin with little contribution from spinal mechanisms [14,19,42]. Noticeably, during cocontraction of opposing muscles, disynaptic reciprocal inhibition has been shown to be reduced by central signals [43,44].…”
Section: Introductionmentioning
confidence: 53%
“…On the one hand, one may consider an end-effector or joint level description of the stiffness-like property of the neuromusculoskeletal system (e.g. [46] or the r-and 190 c-commands in [14]). On the other hand, one may consider more advanced models representing the multiple muscles crossing each joint, the activation of which will modulate both the apparent stiffness of the musculoskeletal system and net joint torques (e.g.…”
Section: Stochastic Optimal Open-loop Control In the Neural Control Omentioning
confidence: 99%
See 3 more Smart Citations